Balanced Nutrition Optimizes Growth and Development of School-Age Children - Dhika Dharmansyah; Dede Lindawati (Indonesian Journal of Community Development, 2021)
Increasing incidence of school-age children with overweight and obesity problems increases the risk of future health problems. This community services provides solutions to introduce balanced nutrition to school-aged children. The method of this activity is community empowerment and training activities. This activity useful for increasing the knowledge, attitudes, and behavior of YWKA elementary school students. The role of community nurses is needed to implement a balanced nutrition program as part of promotional and preventive efforts to prevent problems in children.